Diabetic Ulcer Patients : Literature Review - St. Nur Ashilah Nafi’ah; Prema Hapsari Hidayati; Rizal Basry; Asrini Safitri (Sean Institute, 2025)
Diabetic ulcer can cause infection and decrease the quality of life of sufferers. In patients with diabetic ulcers, it is not uncommon to ignore the nutrients consumed. Though nutrition is very important. If nutritional needs are not met, it can cause several conditions such as anemia (especially iron deficiency anemia), hypoalbuminemia ( due to lack of protein intake ), and malnutrition. In addition, the lack of nutrition intake also affects the inflammatory process in the wound healing phase of diabetic ulcer which, if it continues, can cause more severe infection to the sepsis stage. This literature review aiming to summarize the latest information related to research on nutrition in diabetes ulcer patients. The method used in this study is Literature Reviews by including research on nutrition in diabetes ulcer patients. The keywords used were “ nutrition, macronutrient, micronutrient, diabetes ulcer, diabetic foot ulcers, and venous ulcers ” on websites Google Scholar, Gale, and Pubmed. Results : The results of 32 journals showed inadequate intake of macronutrients (carbohydrates, proteins, and fats ) and micronutrients ( vitamins) and minerals ) in patients with diabetic ulcer which can inhibit the diabetic wound healing process. Nutrients consumed both macronutrients and micronutrients are each needed by the body because they play an important role as a source of energy and play a role in the wound healing process